MODELLING OF INNOVATIVE AND INVESTMENT PROCESSES IN RESORT CITIES AND DESTINATIONS (Development Service Industry Management, 2024)
The innovative development of resort cities and territories is a crucial factor in their competitiveness, economic growth and efficient use of recreational potential. In the context of digitalization and the global transformation of investment flow management, the implementation of modern models based on the principles of the platform economy is necessary for the automation of business processes, optimization of tourist flows and the creation of an effective innovation environment.Development and substantiation of theoretical and methodological approaches to modeling innovation and investment processes in resort cities and destinations, analysis of the role of digital platforms in the modernization of recreational infrastructure and improving the level of services and identification of patterns of innovation adaptation in resort and recreational systems based on a diffusion model.Theoretical and methodological approaches to modeling innovation and investment processes in resort cities and destinations based on the principles of the platform economy are substantiated. The role of digital platforms in the modernization of recreational infrastructure and improving the level of services, in particular, through the implementation of smart solutions for managing tourist flows, optimizing resource use and ensuring sustainable economic growth, is determined. A diffusion model of innovation dissemination in resort and recreational systems is proposed, which takes into account the peculiarities of innovation adaptation in the context of digital transformation and globalization. It is revealed that digital technologies and investment mechanisms, in particular, the platform economy, create prerequisites for the sustainable development of the sanatorium and resort sphere, contributing to its integration into the global tourism market.The research results can be used to develop strategies for the development of resort areas, improve investment policies and implement innovative technologies in the recreational economy. The proposed theoretical and methodological approaches and the model can become the basis for making informed management decisions regarding the innovative development of resort cities and destinations in the context of digitalization and globalization.
Keywords: cities and destinations; investments; innovations; resort; recreation; digitalization; model; platform economy